Reciprocal Trade Liberalization - Kyle Bagwell; Robert W. Staiger (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1996)
Why have governments found reciprocal trade agreements such as GATT to be a more effective means of facilitating trade liberalization than unilateral initiatives? We provide in this paper an analytic framework for the study of reciprocal trade agreements. We use this framework to establish three main results. First, we argue that political-economy factors are important for explaining the range of trade policies observed, but that these factors can not explain why governments seek reciprocal trade agreements as an institutional form for implementing their preferred policies. Rather, whether or not governments are politically motivated, Johnson (1953-54) was right: The central purpose of a reciprocal trade agreement is to eliminate the terms-of-trade driven policies that arise in the absence of such an agreement. Second, we establish an economic interpretation of the principles of reciprocity and nondiscrimination that represent the foundation of postwar reciprocal trade agreements. Finally, we offer new insights regarding the treatment of export subsidies in reciprocal trade agreements.
Keywords: 330